The role of investment opportunity set on financially distressed firm’s value - Tri Nanda, Satria; Zenita, Raisya; Anita, Rizqa; Rasyid Abdillah, Muhammad (International Journal of Engineering and Technology, 2018)
Sustainability of a company is one of them determined by financial performance that is perceived by firm value. Thus it is important to increase firm value as it can be used as signal to investors that the company is worthy. Investment opportunity set and financial distress are one of among factors that affect firm value. This study examines: (1) the influence of investment opportunity set on firm value, 2) the influence of financial distress on firm value and, 3) the role of investment opportunity set as a mediating variable on the relationship between financial distress and firm value. Using PLS Program Warp PLS 5.0., financial data gathered from 33 listing companies of real estate and property sector in Indonesia were analyzed. The results show that Investment opportunity set and financial distress affect firm value. Further analysis found that investment opportunity set play as a mediating variable that mediate the relationship between financial distress and firm value.Â Â